2022
DOI: 10.1002/adma.202203224
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Urinalysis Devices Based on Interface‐Engineered Field‐Effect Transistor Biosensors Incorporated With Electronic Circuits

Abstract: BC diagnosis relies on the insertion of an optical endoscope into the bladder cavity through urethra to image the suspected lesions. [7,8] This process is highly invasive and would cause urethra and bladder injury, resulting in hematuria and even urinary bacterial infection within a few days after examinations. [9] Critically, cystoscopy diagnosis is plagued with the inherent bladder tumor heterogeneity, and therefore, limits the accuracy of early BC diagnosis. [10] Recently, noninvasive liquid biopsy emerges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 54 publications
2
26
0
5
Order By: Relevance
“…The ssDNA-SWNT biosensors could not distinguish between cystitis patients and BCa patients well due to the difficulty in accurately identifying different diseases with a single biomarker (Figure S13). 50,52 From Figure 5c, it can be observed that the miRNA-21 concentration increases with the BCa stages, which is consistent with the upregulated expression theory of BCa. 45,50 This result suggests that the flexible ssDNA-SWNT biosensors might be utilized to give a discrimination.…”
supporting
confidence: 82%
“…The ssDNA-SWNT biosensors could not distinguish between cystitis patients and BCa patients well due to the difficulty in accurately identifying different diseases with a single biomarker (Figure S13). 50,52 From Figure 5c, it can be observed that the miRNA-21 concentration increases with the BCa stages, which is consistent with the upregulated expression theory of BCa. 45,50 This result suggests that the flexible ssDNA-SWNT biosensors might be utilized to give a discrimination.…”
supporting
confidence: 82%
“…The problem is that the extremely high ionic strength of urine samples means the surface charge of target proteins need to be screened from the surrounding charged ions through Debye screening, which decreases the effective charge of the protein and then upsets the identification. Based on this problem and previous research, Yang et al regulated the arrangements of the antibodies on the IGZO surface of the IGZO-FET to minimize the occupied length and reduce the distance between target protein biomarkers and the IGZO channel (Figure 4g) [49]. They compared the performance of the N-terminal functionalized anti-NMP22 IGZO-FET biosensor and the N-terminal functionalized biosensor, which revealed that the N-terminal strategy efficiently minimized the occupied length (Figure 4h), yielded a higher current response toward NMP22 (Figure 4i), and boarded the linear detection range in the 10 × 10 −3 M PBS, which had the equivalent ionic strength to the urine (Figure 4j).…”
Section: Field-effect Transistor (Fet)mentioning
confidence: 98%
“…Recently, Yang et al [ 48 ] proposed a biosensor integrated with a machine-learning algorithm based on IGZO-FET to detect BC in clinical urine samples. The proposed biosensor array can be also incorporated with the electrical circuit to achieve a portable device for POC applications.…”
Section: Detecting Other Biomolecules In Urine Samplementioning
confidence: 99%